Daily stress-influence dynamics predict relationship satisfaction in post-stroke couples - Birthelmer, Sierra; Zambrano Garza, Elizabeth; Pauly, Theresa; Murphy, Rachel A.; Ashe, Maureen C.; Madden, Kenneth M.; Linden, Wolfgang; Gerstorf, Denis; DeLongis, Anita; Hoppmann, Christiane A. (Frontiers in Psychology, 2025)
IntroductionSignificant health events, such as a stroke, not only impact the individual themselves but also significant others, such as partners. This study examines the daily life associations between stress and relationship satisfaction in couples post-stroke, and the potential buffering effect of perceived equal relationship influence.MethodsWe analyzed data from 85 Canadian couples in whom at least 1 partner experienced a stroke. Both members of the dyads provide simultaneous stress and relationship satisfaction ratings for up to 14 consecutive days. Relationship influence was measured once. We fit three nested two-level actor–partner interdependence models.ResultsElevated stress was associated with lower same-day relationship satisfaction at both within- and between-person levels. Furthermore, higher daily partner stress was associated with lower actor relationship satisfaction on the same day, over and above one’s daily stress. Finally, an equal relationship influence buffered the negative effects of partner stress on relationship satisfaction for stroke survivors.ConclusionThis study highlights the complex interplay between daily stress, relationship satisfaction, and relationship influence in couples living with the effects of a stroke. Findings underscore the importance of considering the balance of power in relationships, as stroke survivors and their partners face distinct challenges that shape their daily relational experiences.